China experiments from local innovations to national reform - Florini, Ann.; Lai, Hairong; Tan, Yeling; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2012)
"Using detailed and empirically grounded analysis, examines the changing relationship between the Chinese state and the society it governs, how governance choices made affect the country and the rest of the world, and how local Chinese authorities have responded to the challenges they face in coping with China's rapid transformation"--Provided by publisher.
Preface -- China at a crossroads -- Streamlining the state -- The evolution of voting mechanisms -- Civil society -- From local experiments to national rules: China lets the sunshine in -- Where is China going?.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Public administration -- China; Organizational change -- China; Central-local government relations -- China; Decentralization in government -- China; Local government -- China; Electronic books